A point-of-care assay for genotyping women prior to ovarian stimulation with recombinant or human menopausal gonadotropins in assisted reproduction - Nilsson, Mathilda; Hjelmér, Ida; Prahl, Alexandra; Nenonen, Hannah; Lundberg Giwercman, Yvonne (Frontiers in Endocrinology, 2026)
ObjectivePrior to in vitro fertilization (IVF), physicians can choose either recombinant or urine-derived follicle-stimulating hormone (FSH) for ovarian stimulation. The common polymorphism N680S (rs6166) in the follicle-stimulating hormone receptor (FSHR) has been linked to individual variability in ovarian response to FSH stimulation and IVF outcomes, including live birth rates, highlighting its potential value in optimizing stimulation protocols. However, classical genotyping is laborious, often requiring blood as starting material and specialized laboratories for analysis. The aim of the study was to develop a system for rapid and easy-to-use genotyping of the FHSR N680S variant.MethodsThe assay constituted an allele-specific peptide nucleic acid-mediated loop-mediated isothermal amplification (AS PNA-mediated LAMP) assay with a colorimetric detection system. The analytical performance was analyzed with naked-eye detection and verified with fluorescence amplification. Clinical validation was assessed on 50 patients visiting an IVF-clinic in whom the variant was confirmed with Sanger sequencing.ResultsNinety-one out of 100 samples were genotyped correctly, demonstrating 91% overall accuracy. Clinical sensitivity reached 86.8 [95% Cl 76.4-93.8%], while specificity was 100% [95% Cl 89.1-100%]. The test was performed by trained laboratory staff in less than one hour.ConclusionThe LAMP assay provides a rapid and user-friendly genotyping of the FSHR N680S, which makes it a valuable tool in point-of-care settings, where it may help guide treatment options prior to IVF.